Enhanced MAC protocol for designing a wireless sensor network based on a single LEO Picosatellite. (2017) - Addaim, Adnane; Kherras, Abdelhaq; Guennoun, Zouhair
In this paper, we address the design of a wireless sensor network (WSN) using a single low earth orbit (LEO) satellite. The satellite, as small as a Picosatellite, requires employment of a very simple payload whereas all the complexity is brought back to the relay nodes (RNs), which are connected directly to the Picosatellite using a multiple access protocol. An improvement protocol to enhance the performance of Slotted Aloha, based on collision avoidance after first successful transmission, is proposed. We establish a mathematical model for evaluating the performance of the proposed protocol with collision avoidance termed as Slotted AlohaCA. Two appropriate performance measures are evaluated: Throughput and Energy efficiency. In the model, each RN has M packets to send during the visibility period of the Picosatellite. The proposed scheme approaches the maximum throughput of 100% for high value of M and hence improves significantly the energy efficiency compared with the traditional Slotted Aloha protocol owing to collision avoidance.